Water metal contaminants in a potentially mineral-deficient population of Haiti. Issue 6 (2nd November 2018) - Rivera-Núñez, Zorimar; Pan, Zezhen; Dulience, Bazelais; Becker, Haley; Steensma, Joe; Hobson, Angela; Giammar, Daniel E.; Iannotti, Lora L.
ABSTRACT: This study aimed to characterize metal contaminant concentrations and assess temporal and spatial variability in the main drinking water sources of Cap-Haïtien, Haiti. Water sources from five communities were sampled in two seasons, June (2014) and October (2014), and analysed for a suite of metals. A geographic information system was used to examine the spatial distribution of sampling points. Metal concentrations were below the US Environmental Protection Agency (USEPA) primary drinking water standards. Mean manganese concentrations were comparatively higher in wells (254.5 µg/L), exceeding the USEPA secondary drinking water standard (50 µg/L). Higher mean Mg/Ca and Ba/Ca ratios (range 2.3–3.4) may indicate different interactions between seawater and groundwater throughout the year. Although metal concentrations were within the limits of the USEPA drinking water standards, emerging contaminants, such as manganese, showed concentrations in excess of recommended limits. These metals may interact with background nutritional status with potential implications for growth and development.